Neuropsychiatric disturbance detecting polycythemia vera myelofibrosis: a case report and literature review - Li, Li; Zhou, Min; Wu, Yun-Qin; Fan, Wei-Nv; Li, Da (Frontiers in Neurology, 2023)
Background Neuropsychiatric disturbances and chorea are less recognized consequences of polycythemia vera (PV), and their role in post-PV myelofibrosis (MF) has not been reported. Clinical features that predict post-PV MF lack specificity. Case presentation We describe an elderly patient with PV who developed acute-onset reversible neuropsychiatric disturbances accompanied by generalized chorea and was finally diagnosed with post-PV MF after a bone marrow examination. We also reviewed four cases of late PV associated with neuropsychiatric symptoms since 1966 and analyzed their clinical characteristics and therapeutic effects. Conclusion Our case indicates that Janus kinase 2 (JAK2)-related PV is a treatable cause of late-onset chorea and that chorea may herald the deterioration of hematological parameters. Our case provides a clinically specific representation of post-PV MF. Patients with a long course of PV are recommended to undergo bone marrow re-examinations when they present with neuropsychiatric symptoms to achieve an early diagnosis of post-PV MF.